Our sixth-grade sugar babies - Bunting, Eve, 1928- (New York : HarperCollins Publisher, 1990)
Vicki and her best friend fear that their sixth grade project, carrying around five-pound bags of sugar to learn about parental responsibility, will make them look ridiculous in the eyes of the seventh grade boy they both love.
Keywords: Schools -- Fiction